Solid surface-mediated photochemical transformation of decabromodiphenyl ether (BDE-209) in aqueous solution. (15th November 2017) - Qu, Ruijuan; Li, Chenguang; Pan, Xiaoxue; Zeng, Xiaolan; Liu, Jiaoqin; Huang, Qingguo; Feng, Jianfang; Wang, Zunyao
Abstract: Polybrominated diphenyl ethers (PBDEs) are brominated flame retardants which have received considerable attention due to their global distribution, bioaccumulation potential, environmental persistence, and possible toxic effects. In this work, the photodegradation of decabromodiphenyl ether (BDE-209) in aqueous system was investigated by preloading it on the surface of various solid matrices. After 6 h of Xe lamp irradiation, almost complete degradation of BDE-209 was observed on silica gel (SG), with much slower degradation occurring in other adsorbents. The degradation of BDE-209 on SG sample followed pseudo-first-order kinetics, and the observed reaction rate constant was decreased by lowering pH, adding humic acid and increasing the initial BDE-209 concentration. In addition to direct photolysis, BDE-209 could be oxidized by hydroxyl radicals generated from SG, as confirmed by the electron paramagnetic resonance (EPR) technology. Product analysis showed that BDE-209 was mainly decomposed into lower brominated PBDEs, polybrominated dibenzofurans (PBDFs), hydroxylated PBDEs (OH-PBDEs), hydroxylated PBDFs (OH-PBDFs), bromophenols and bromide ions. Thus, consecutive debromination, intramolecular elimination of HBr, hydroxyl addition and the cleavage of ether bond were proposed as the degradation pathways. This study may help understanding the photochemical transformation of solid surface adsorbed BDE-209 in natural surface waters, which is important to evaluate the environmental fate of PBDEs. Graphical abstract: Highlights: Photodegradation of BDE-209 adsorbed onto various solids in water was studied. BDE-209 removal depends on sorbent with most efficient degradation on silica gel. Effect of pH, HCO3 −, NO3 −, HA, sample dosage, surface coverage was examined. Both direct photolysis and photooxidation by hydroxyl radicals are involved.